Composición química y enzimas digestivas en juveniles de tilapia roja (Oreochormis mossambicus x Oreochromis niloticus) alimentados con β-glucano - Costavalo Muñoz, Johana Amarilis (2021)
The main chemical components of tilapia meat are closely related to feeding, being an important factor concerning the nutritional value of the meat, storage capacity and digestion and absorption processes. The present research work aims to evaluate the chemical composition and digestive enzyme activity in juvenile red tilapia (Oreochormis mossambicus x Oreochromis niloticus) with the inclusion of β-glucan in diets, was conducted in the aquaculture and bromatological laboratory at the campus "La Maria", belonging to the FCA of the State Technical University of Quevedo, with a duration of 60 days, for which 6 treatments and three replicates were used in a DCA. Structured with an experimental diet with supplementation at different levels of β-glucan of 0 (control), 1, 2, 3, 3, 4 and 5 %. All analyses were performed on a dry basis at laboratory level, the chemical composition of the muscle of juvenile red tilapia, obtained higher averages in dry matter with 25.35%, carbohydrates with 38.97% and ash 2.44%, with the supplementation of 0% β-glucan in the diet, with respect to the protein variable had a higher percentage in T6 with 74.94%, with the inclusion of 5% β-glucan. Regarding lipids, the highest percentage of fats was established in treatment T5 with 5.73%. In the digestive enzymatic activities analyzed in the intestines of the juveniles, protease showed lower activity in T3 with 38.14%, with the supplanting of 3% of β-glucan, for lipase it showed higher percentage of activity in T6 with 42.28%, and amylase registered in T5 with 79.82% being lower than the other treatments. A relationship was established between lipolytic and aminolytic activities as the inclusion of β-glucan increases, while proteolytic activity occurred in T4 and T6. Key words: polysaccharides, proteases, proteins, pelleted diets, nutrition.